Integrating Internal Control and User Competence: Enriching Accounting Information System Quality - Rapina, Rapina; Mustamin, Nurul Intawaty Permata (Universitas Kristen Maranatha, 2024)
Purpose - This study aims to investigate how user competency and internal controls help to improve the quality of accounting information systems (AIS) in enterprises. The study intends to discover how these characteristics influence the usefulness of the Accounting Information System notably with respect to financial data quality overall decisions being made. Design/methodology/approach - The focus of this study discusses the data that has been taken from 94 respondents registered as civil servants at several departments in PT Pos Indonesia. To analyze this relationship of user competency, internal controls and AIS quality a research methodology for the investigation into Partial Least Square-Structural Equation Modeling (PLS-SEM) is adopted. Findings - The findings of PLS-SEM analysis reveal that they both seem to play significant roles in enhancing the quality level of AIS. Proficient operators will be able to navigate the system easily, input data accurately and interpret outputs properly thus lowering mistakes in financial reporting. To ensure data integrity, control fraud and keep a clean system of record various internal controls such as dual verification, segregation of roles or regular audits are essential. Research limitations/implications - The study refers to the responses given by PT Pos Indonesia so it is not generalisable for other organizations or industries. Further study should consider businesses having different scales of operations to increase the validity in results. From a practical standpoint, the study has implications for investing in users training and development as well as on setting up strong internal control mechanisms to reduce AIS performance shortfall that influences judgment making reasoning within organizations. These require integrity, a strong fraud prevention and transaction record keeping. Keywords: User Competence, Internal Controls, PLS-SEM